Translanguaging In Social Media : A Case Study Of Zhafira Aqila’s Youtube Channel - Amalia Rosyidah Misbah; Syamsudin Syamsudin (Utan Kayu Publishing, 2024)
This study aims to investigates the use of translanguaging by Indonesian students who are continuing their education in the United States. The research was motivated by the rampant use of translanguaging, especially through the use of social media such as YouTube. The study examines forms of translanguaging, including code-switching (CS), code-mixing, and multimodal communication, as well as the functions these serve in shaping audience engagement. Through a qualitative descriptive analysis of three videos, the research identifies that code-switching is the most prominent component, appearing in 82% of